2022
DOI: 10.1017/cts.2022.510
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and solutions for representative inclusion across the lifespan and in life course research: The need for structural competency highlighted by the COVID-19 pandemic

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 117 publications
1
8
0
Order By: Relevance
“…This is in line with previous research that has suggested that financial incentives can be used to boost recruitment among underrepresented groups, specifically Hispanic participants [33]. A recent thematic review also noted that increased benefits such as reimbursements for transportation costs and monetary incentives are a potential mechanism to increase representation of people from racial and ethnic minority groups [21]. CRCs also reported that study location frequently factored into participants’ willingness to participate in clinical research studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with previous research that has suggested that financial incentives can be used to boost recruitment among underrepresented groups, specifically Hispanic participants [33]. A recent thematic review also noted that increased benefits such as reimbursements for transportation costs and monetary incentives are a potential mechanism to increase representation of people from racial and ethnic minority groups [21]. CRCs also reported that study location frequently factored into participants’ willingness to participate in clinical research studies.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Non-Hispanic Black participants were more likely to report the role of trust/mistrust in their decision to participant in clinical research studies, while Hispanic participants reported that incentives play a more key role in their decisions [19,20]. A recent review of barriers to representation in research noted that among racial and ethnic minority groups, salient barriers included trust and confidentiality, lack of access to available studies, and challenges with participant contact and scheduling [21]. Other key drivers of underrepresentation in research include language barriers such as unavailability of translated study materials, competing work and caregiving responsibilities, and costs of participation such as transportation [17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several other papers outline strategies and approaches for improving recruitmentincluding training and hiring community members to do clinical research, standardizing best practices for community health workers, providing new pathways for clinical research within a medical assistant training program, and providing cultural humility training and supportive environments for clinical research coordinators [19][20][21]. Using principles of structural competency and structural humility, LeCroy et al propose research interventions should directly address barriers to research participation within and across special populations based on geographic, socioeconomic, and individual constraints by accounting for them within the study design and giving staff more flexibility and resources to accommodate participants [22]. Smith et al remind researchers that while increasing diversity in recruitment efforts is critical to addressing health disparities among affected populations, fair subject selection, and ethical considerations must be applied to ensure fair inclusion, fair burden sharing, and fair opportunity providing historical examples and how the concept was applied to post-sequelae COVID-19 translational studies [23].…”
Section: Health Equity Researchmentioning
confidence: 99%
“…Participants with less-flexible work schedules may require childcare to enable their participation [ 13 ]. Yet, many families are unable to afford childcare, and/or the availability of childcare can be limited, especially in rural areas [ 14 ]. Although some research groups can provide onsite childcare, many sites do not have access to a pool of volunteers (e.g., undergraduate or graduate students) or a child-friendly space.…”
Section: Introductionmentioning
confidence: 99%